2006
DOI: 10.1136/oem.2005.023200
|View full text |Cite
|
Sign up to set email alerts
|

The French National Mesothelioma Surveillance Program

Abstract: The NMSP is a large scale epidemiological surveillance system with several original aspects, providing important information to improve the knowledge of malignant pleural mesothelioma, such as monitoring the evolution of its incidence, of high risk occupations and economic sectors, and improving pathology techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
137
1
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 13 publications
12
137
1
11
Order By: Relevance
“…10% of the cases regularly registered. 22 However, when restricted to the PNSM data, a levelling off trend is also apparent, suggesting that the evolution of the incidence of pleural cancers was only partially explained by a modification in registration practices within registries or by the improvement of the pathological diagnosis of mesothelioma. This does not seem to be the case for women, for which the increasing trend of incidence seems to be largely explained by under diagnosis between 1980 and 1997.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10% of the cases regularly registered. 22 However, when restricted to the PNSM data, a levelling off trend is also apparent, suggesting that the evolution of the incidence of pleural cancers was only partially explained by a modification in registration practices within registries or by the improvement of the pathological diagnosis of mesothelioma. This does not seem to be the case for women, for which the increasing trend of incidence seems to be largely explained by under diagnosis between 1980 and 1997.…”
Section: Discussionmentioning
confidence: 99%
“…The PNSM main procedures have been described in detail elsewhere. 22 Twenty-one districts were selected for this program (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies in other countries reported higher risks in plumbers, electricians and other construction workers than in carpenters (Muscat and Wynder, 1991;Teschke et al, 1997;Rodelsperger et al, 2001). Among construction workers, preliminary results of a French populationbased case -control study show the highest risks in plumbers, pipe fitters, structural steel workers and construction labourers (Goldberg et al, 2006). In a large non-interview study in California based on main occupation of over 2000 mesothelioma cases and pancreatic cancer controls, increased ORs were seen for plumbers (OR ¼ 4.9, 95% CI 2.8 -8.3), electricians (OR ¼ 3.8, 95% CI 2.0, 7.1) and painters (OR ¼ 2.6, 95% CI 1.3 -5.3) but not for carpenters (OR ¼ 1.2, 95% CI 0.8 -2.0) (Pan et al, 2005).…”
Section: All Asbestos Exposuresmentioning
confidence: 99%
“…A panel of French thoracic pathologists reviewed 1/3 of all mesothelioma diagnoses in France in the previous year and confirmed the diagnoses in only 67% of them (3). In a recent study in collaboration with experts of thoracic pathology in China, we reviewed the diagnoses of mesothelioma in Eastern China and confirmed the diagnoses in 56.5% of them.…”
Section: Pathologymentioning
confidence: 99%